CD8+ NKs as a potential biomarker of complete response and survival with lenalidomide plus R-GDP in the R2-GDP-GOTEL trial in recurrent/refractory diffuse large B cell lymphoma - Hontecillas-Prieto, Lourdes; García-Domínguez, Daniel J.; Palazón-Carrión, Natalia; Martín García-Sancho, Alejandro; Nogales-Fernández, Esteban; Jiménez-Cortegana, Carlos; Sánchez-León, María L.; Silva-Romeiro, Silvia; Flores-Campos, Rocío; Carnicero-González, Fernando; Ríos-Herranz, Eduardo; de la Cruz-Vicente, Fátima; et al. (Frontiers in Immunology, 2024)
Background: Diffuse large B cell lymphoma (DLBCL) is the most common non-Hodgkin lymphoma worldwide. DLBCL is an aggressive disease that can be cured with upfront standard chemoimmunotherapy schedules. However, in approximately 35-40% of the patients DLBCL relapses, and therefore, especially in this setting, the search for new prognostic and predictive biomarkers is an urgent need. Natural killer (NK) are effector cells characterized by playing an important role in antitumor immunity due to their cytotoxic capacity and a subset of circulating NK that express CD8 have a higher cytotoxic function. In this substudy of the R2-GDP-GOTEL trial, we have evaluated blood CD8+ NK cells as a predictor of treatment response and survival in relapsed/refractory (R/R) DLBCL patients. Methods: 78 patients received the R2-GDP schedule in the phase II trial. Blood samples were analyzed by flow cytometry. Statistical analyses were carried out in order to identify the prognostic potential of CD8+ NKs at baseline in R/R DLBCL patients. Results: Our results showed that the number of circulating CD8+ NKs in R/R DLBCL patients were lower than in healthy donors, and it did not change during and after treatment. Nevertheless, the level of blood CD8+ NKs at baseline was associated with complete responses in patients with R/R DLBCL. In addition, we also demonstrated that CD8+ NKs levels have potential prognostic value in terms of overall survival in R/R DLBCL patients. Conclusion: CD8+ NKs represent a new biomarker with prediction and prognosis potential to be considered in the clinical management of patients with R/R DLBCL. Clinical trial registration: EudraCT, ID:2014-001620-29